Multidisciplinary reconstructive management of residual recalcitrant empyema cavity: A retrospective observational cohort study. Issue 3 (March 2022) - Allen, Luke CE; Milton, Richard; Bourke, Grainne
Summary: Background: Patients with stage III empyema require chest wall fenestration to enable lung re-expansion and continuous drainage of the persisting empyema cavity. This chronic wound negatively affects patients' exercise tolerance, ability to carry out activities of daily living, and quality of life. Methods: Eight consecutive patients underwent chest wall reconstruction following fenestration and were followed up over a minimum of 12 months. This study included adult patients (over 18 years of age). There were no exclusion criteria. Data were collected retrospectively. Results: Eight patients (six male and two female), with a mean age of 56 years (range, 22–76), were included. All of them had comorbidities including history of neoplasia ( n = 6), atrial fibrillation ( n = 3), and hypertension ( n = 2). Aetiology of empyema included lung cancer resection complicated by bronchopleural fistula ( n = 4), pneumonia ( n = 2), and pleural effusion ( n = 2). Five patients had a low metabolic reserve evident by a low BMI (range, 16–22), and a median malnutrition universal screen tool (MUST) score of 2 (range, 1–4). Following intensive infection control and nutritional support, patients underwent reconstruction 11 months (median; range 5–51) after fenestration. Seven patients were followed up and had no recurrence of empyema and bronchopleural fistula. They all reported significant improvements in their quality of life, and their Eastern Cooperative Oncology Group (ECOG) performance status improved from three to one. One patient died 56 days post-reconstruction from cardiorespiratory failure, which required readmission to hospital. Conclusion: We demonstrate that free tissue reconstruction including multidisciplinary input and optimisation at all stages of care successfully closes residual recalcitrant empyema cavity without recurrence and leads to significant improvements in the quality of life.